Regionale und sektorale Kapitalströme als Folgeerscheinung der Remigration türkischer Arbeitskräfte aus Westeuropa - Toepfer, Helmuth (ERDKUNDE, 1981)
a) Though urban re-migrants (returning labourers who aim at settling in small towns) regard the chances of securing an existence in their places of residence as being very good, those returning to villages recognize that the investment of much of their capital is meaningful only outside their home area in small and large towns (Kg.l). b) The economic position of re-migrants depends to a high degree on the regional and sectoral structure of the capital investment, but less on its size. c) A follow-up of the capital invested capital of re-migrants showed that the effect of the flow of capital into the area under investigation is only short-lived. At the first re-deployment a large part of the capital invested by the re-migrants moves into the large towns outside the study area (Fig. 2).